Non-Cardiogenic Pulmonary Edema and Acute Respiratory Failure after Right Heart Catheterization: A Rare Complication with A Diagnostic Dilemma - KARAKURT, SAİT; ERYÜKSEL, SEMİHA EMEL (AVES, 2018)
Although right heart catheterization (RHC) is generally a safe procedure, serious adverse events can occur during the procedure. We report a case of non-cardiogenic pulmonary edema and respiratory failure after RHC to assess pulmonary arterial hypertension in a patient who was a candidate for lung transplantation and discuss the differential diagnosis of pulmonary edema.
Keywords: Pulmonary edema; respiratory failure; air embolism; right heart catheterization; HYPERTENSION